2016
DOI: 10.1016/j.scr.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB3 restricts endogenous neural stem cell migration after traumatic brain injury

Abstract: Traumatic brain injury (TBI) leads to a series of pathological events that can have profound influences on motor, sensory and cognitive functions. Conversely, TBI can also stimulate neural stem/progenitor cell proliferation leading to increased numbers of neuroblasts migrating outside their restrictive neurogenic zone to areas of damage in support of tissue integrity. Unfortunately, the factors that regulate migration are poorly understood. Here, we examine whether ephrinB3 functions to restrict neuroblasts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…It is likely that EphB3-mediated OL cell death plays a major role in the observed functional deficits associated with CCI injury; however, we cannot rule out the possibility that multiple cell types may contribute to the improved behavioural functions associated with EphB3 deletion or ephrinB3 administration. In particular, improved survival of neural progenitor cells and endothelial cells may stabilize the blood–brain barrier and injury microenvironment ( Dixon et al , 2016 ; Assis-Nascimento et al , 2018 ). We have also shown that EphB3 signalling may have deleterious effects on synaptic stability after TBI, suggesting that decreased EphB3 activity may reduce the global dysfunction of networks in the injured brain ( Perez et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that EphB3-mediated OL cell death plays a major role in the observed functional deficits associated with CCI injury; however, we cannot rule out the possibility that multiple cell types may contribute to the improved behavioural functions associated with EphB3 deletion or ephrinB3 administration. In particular, improved survival of neural progenitor cells and endothelial cells may stabilize the blood–brain barrier and injury microenvironment ( Dixon et al , 2016 ; Assis-Nascimento et al , 2018 ). We have also shown that EphB3 signalling may have deleterious effects on synaptic stability after TBI, suggesting that decreased EphB3 activity may reduce the global dysfunction of networks in the injured brain ( Perez et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the extent of circulating macrophage infiltration within the pancreas, the immunohistochemistry images were quantitated for the level of IBA-1 expression [ 39 , 40 ]. Images were imported into ImageJ software (NIH), converted to gray scale, thresholded, and the area fraction of pixels positive for IBA-1 was quantitated, the values for each photograph were averaged per section, per animal, and then per group [ 41 , 42 ]. The same protocol was applied to brain sections containing hippocampus at 7 days post-induction to quantitate astrocyte reactivity using the GFAP antibody.…”
Section: Methodsmentioning
confidence: 99%
“…In rodents, the SVZ is a thin ‘wedge’ of cells, covering the entire wall of the lateral ventricle (Mirzadeh et al ., 2010; Paez-Gonzalez et al ., 2014; Dixon et al ., 2016). Within the SVZ the slow-dividing astrocyte-like type B cells differentiate into rapidly dividing type C neural progenitor cells (also known as transit amplifying cells) that give rise to double-cortin-positive type A neuroblasts, although oligodendrocytes and astrocytes are also capable of being produced (Garcia-Verdugo et al ., 1998; Tavazoie et al ., 2008; Rikani et al ., 2013).…”
mentioning
confidence: 99%
“…Ablation studies suggest it takes approximately 2 days for fast dividing type C neural progenitor cells to populate the SVZ, and an additional 2.5 days for neuroblasts to appear (Doetsch et al ., 1999). A small percentage of these neuroblasts are capable of migrating ectopically out of the RMS into surrounding tissues in naïve mice; however, this phenomenon is drastically increased following brain injury (Dixon et al ., 2016). The ability of neuroblasts to redirect their migratory routes towards damaged tissues has been shown to have beneficial effects on brain recovery (Li et al ., 2010; Dixon et al ., 2015), which can occur as early as 3 days post-injury (Ramaswamy et al ., 2005; Dixon et al ., 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation